Knowledge, attitudes and habits regarding oral health among nurses of Clinical hospital center Rijeka : Znanja, navike i stavovi medicinskih sestara / tehničara Kliničkog bolničkog centra Rijeka o oralnom zdravlju - Ivančić Jokić, Nataša (Array, 2021)
Background/Aim: The aim of this study was to investigate oral health knowledge, attitudes and habits regarding oral health among nurses and to evaluate if there is a difference in self-reported oral health behavior in relation to the degree of professional education. Methods: The study was conducted on a sample of 100 subjects, both gender, aged 22 to 62. The respondents were nurses with completed secondary school (49%) and nurses with bachelor"s or master"s degrees in nursing (51%). The study was conducted via the Croatian version of the Hiroshima University-Dental Behavioral Inventory (HU-DBI) questionnaire. Results: Nurses with a bachelor"s or master"s degree had a significantly higher HU-DBI score than nurses with completed secondary school (p=0.033). Statistically significant difference was found in the following questions: I brush each of my teeth carefully (p=0.026), I put off going to the dentist until I have a toothache (p=0.008) and I have had my dentist tell me that I brush very well (p=0.016). Conclusion: The obtained results show that healthcare professionals with higher education (bachelor"s or master"s degree in nursing) have more knowledge on oral health and that they apply this knowledge in their daily oral hygiene routine.